2015
DOI: 10.1161/strokeaha.115.010767
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Mouse and Human Studies Implicate ANGPT1 and ZBTB7C as Susceptibility Genes to Ischemic Injury

Abstract: Background and Purpose The extent of ischemic injury in response to cerebral ischemia is known to be affected by native vasculature. However, the non-vascular and dynamic vascular responses and their genetic basis are not well-understood. Methods We performed a genome-wide association study in 235 mice from 33 inbred strains using the middle cerebral artery occlusion model. Population structure and genetic relatedness were accounted for by using the efficient mixed-model association method. Human orthologs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…Interestingly, the FOXO families of transcription factors have previously been implicated in AD pathogenesis by influencing neuronal survival 43 and Aβ-induced neuroinflammation 44 . ZBTB7C has also been suggested as a susceptibility gene for ischemic stroke through modulation of neuronal apoptosis 45 . Finally, a paternally inherited translocation of ZBTB7C has been associated with non-syndromal mental retardation in male twins 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the FOXO families of transcription factors have previously been implicated in AD pathogenesis by influencing neuronal survival 43 and Aβ-induced neuroinflammation 44 . ZBTB7C has also been suggested as a susceptibility gene for ischemic stroke through modulation of neuronal apoptosis 45 . Finally, a paternally inherited translocation of ZBTB7C has been associated with non-syndromal mental retardation in male twins 46 .…”
Section: Discussionmentioning
confidence: 99%
“…They also corrected for weight and age, strengthening the argument for genetic causality. The same authors previously explored the genetic basis for these vascular differences and identified 4 SNPs associated with infarct volume in mice after middle cerebral artery occlusion, 2 of which were relevant to human stroke susceptibility [16].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding susceptibility or resistance to injury based on genetic background in mice should not only improve research methods but also our understanding of human variation in injury outcome, and it may ultimately lead to novel targets for intervention [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…At the microvascular level, the number and diameters of collateral vessels between the anterior cerebral artery (ACA) and middle cerebral artery (MCA) have been shown to differ across strains (Maeda et al, 1998 ; Zhang et al, 2010 ). In addition, the susceptibility to ischemia and the percentage of total cortical surface area supplied by the MCA, ACA, and posterior cerebral artery (PCA) can differ significantly across mouse strains (Sheldon et al, 1998 ; Majid et al, 2000 ; Zhang et al, 2010 ; Du et al, 2015 ). Several strains have been utilized for murine stroke models (Hata et al, 1998 ; Orset et al, 2007 ; Zhang et al, 2010 ; Du et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%